2019
DOI: 10.1002/pmic.201900095
|View full text |Cite
|
Sign up to set email alerts
|

Protective Cellular Mechanism of Estrogen Against Kidney Stone Formation: A Proteomics Approach and Functional Validation

Abstract: Females have less incidence/prevalence of kidney stone disease than males. Estrogen thus may serve as the protective factor but with unclear mechanism. This study explores cellular mechanism underlying such stone preventive mechanism of estrogen. Madin darby canine kidney (MDCK) renal tubular cells are incubated with or without 20 nm 17β‐estradiol for 7 days. Comparative proteomics reveals 58 differentially expressed proteins in estrogen‐treated versus control cells that are successfully identified by nanoLC–E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“… 26 As for estradiol, its role in protecting the kidneys against crystal damage has been proved, based on the mechanism of decreasing surface expression of CaOx crystal receptors, reducing intracellular metabolism, and enhancing cell proliferation and tissue healing. 27 In addition, progesterone has been reported to affect parathyroid hormone transcription, which regulated the balance of water and salt. 28 Besides, by promoting bone formation and bone turnover, progesterone lowered calcium levels in blood and urine.…”
Section: Discussionmentioning
confidence: 99%
“… 26 As for estradiol, its role in protecting the kidneys against crystal damage has been proved, based on the mechanism of decreasing surface expression of CaOx crystal receptors, reducing intracellular metabolism, and enhancing cell proliferation and tissue healing. 27 In addition, progesterone has been reported to affect parathyroid hormone transcription, which regulated the balance of water and salt. 28 Besides, by promoting bone formation and bone turnover, progesterone lowered calcium levels in blood and urine.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A1 that is highly expressed in epithelial cells of polyps can bind COM crystal in the urine to the surface of calculi through its transmembrane domain. [ 18 , 19 ] Alternatively, it can bind oxalic acid and calcium ions in the urine through its target protein S100 A9, which may be realized by EF-hand motifs in the S100 A9 domain. [ 4 , 20 ] In our study, correlation analysis of the H-score of annexin A1/S100 A9 indicated a strong correlation between the expressions of the 2 proteins; this suggested a synergistic relationship between annexin A1 and S100 A9 in binding COM crystal.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 17 suggested a protective mechanism of estrogen against stone formation. They reported that incubating renal tubular cells with 17β-estradiol for 7 days resulted in changes in cellular proteome of the renal tubular cells and a consequent decrease in surface expression of calcium-oxalate crystal receptors, decreased intracellular metabolism, and enhanced cell proliferation and tissue healing, altogether assumed to contribute to stone formation prevention.…”
Section: Discussionmentioning
confidence: 99%